2022
DOI: 10.1002/adma.202108581
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency of over 25% and Long Device Lifetime of over 500 h at 1000 nit in Blue Fluorescent Organic Light‐Emitting Diodes

Abstract: In this study, a multiple resonance (MR) type blue emitter is synthesized, characterized, and evaluated for highly efficient and stable blue fluorescent organic light‐emitting diodes (OLEDs). The MR blue fluorescent emitter has a di‐tert‐butyl benzene substituent in the MR core structure to minimize quenching mechanisms by intermolecular interaction. The emitter shows a high photoluminescence quantum yield and small full width at half maximum of 22 nm, which realize high external quantum efficiency (EQE) of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…In 2022, Lee et al reported MR‐TADF blue emitter ( t‐DABNA‐dtB ) by introducing di‐tert‐butyl benzene substituent in the MR core ( t‐DABNA ) to minimize the quenching mechanisms by restricting the intermolecular interaction. [ 105 ] The designed emitter showed a high PLQY and small FWHM ≈ 22 nm, which realized high EQE of 11.4% in the single unit OLED with operational lifetime LT 95 of 208 h at 1000 cd m −2 and over 10 000 h at 100 cd m −2 . The t‐DABNA‐dtB displayed pure blue emission λ EL ≈ 470 nm with a CIEy coordinate of ≈0.13.…”
Section: Blue/deep‐blue Mr‐tadf Emittersmentioning
confidence: 99%
“…In 2022, Lee et al reported MR‐TADF blue emitter ( t‐DABNA‐dtB ) by introducing di‐tert‐butyl benzene substituent in the MR core ( t‐DABNA ) to minimize the quenching mechanisms by restricting the intermolecular interaction. [ 105 ] The designed emitter showed a high PLQY and small FWHM ≈ 22 nm, which realized high EQE of 11.4% in the single unit OLED with operational lifetime LT 95 of 208 h at 1000 cd m −2 and over 10 000 h at 100 cd m −2 . The t‐DABNA‐dtB displayed pure blue emission λ EL ≈ 470 nm with a CIEy coordinate of ≈0.13.…”
Section: Blue/deep‐blue Mr‐tadf Emittersmentioning
confidence: 99%
“…However, excimer emission or aggregated concentration quenching caused by intermolecular interaction are challenging hurdles due to planar structural characteristics. 18–22 Based on 5,9-diphenyl-5,9-diaza-13 b -boranaphtho[3,2,1- de ]anthracene (DABNA-1), various derivatives have been reported in which the emission wavelength and photophysical properties of materials are controlled. 23–33 For example, Wang and coworkers reported a t -butyl carbazole substituted emitter (DtBuCzB) instead of a diphenylamine modified one.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Doping is a common method for tuning and controlling the charge-carrier density in organic semiconductors (OSCs). The doping process is crucial for the functioning of organic light-emitting diodes, [12][13][14] organic field-effect transistors, 15,16 organic photovoltaics, 17 organic thermoelectrics, 18 etc. Consequently, a large number of studies on doping for conjugated organic materials have been carried out, resulting in exceptionally high electrical conductivity values that exceed 1000 S cm À1 .…”
Section: Introductionmentioning
confidence: 99%